2014
DOI: 10.1186/1472-6947-14-97
|View full text |Cite
|
Sign up to set email alerts
|

Ambient-aware continuous care through semantic context dissemination

Abstract: BackgroundThe ultimate ambient-intelligent care room contains numerous sensors and devices to monitor the patient, sense and adjust the environment and support the staff. This sensor-based approach results in a large amount of data, which can be processed by current and future applications, e.g., task management and alerting systems. Today, nurses are responsible for coordinating all these applications and supplied information, which reduces the added value and slows down the adoption rate.The aim of the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…In the measurement we did not include the time needed for this registration as this heavily depends on the complexity of the filter rule, the amount of filter rules already present in the SCB and the size of the ontology used by the SCB. This was already thoroughly evaluated in previous research [31], which has shown that in most realistic scenarios this time is under 1 second.…”
Section: Evaluation Of Quality Attribute Scenariosmentioning
confidence: 98%
“…In the measurement we did not include the time needed for this registration as this heavily depends on the complexity of the filter rule, the amount of filter rules already present in the SCB and the size of the ontology used by the SCB. This was already thoroughly evaluated in previous research [31], which has shown that in most realistic scenarios this time is under 1 second.…”
Section: Evaluation Of Quality Attribute Scenariosmentioning
confidence: 98%
“…There is one LRS per room, independent of the amount of patients. Over the full hospital, only one BRS exists 4 .…”
Section: Architectural Use Case Set-upmentioning
confidence: 99%
“…Moreover, the ontology contains some concepts for this use case that allow the inference of certain situations and hence easier query writing. An example is NursePresentObservation, which is defined as a BLE tag observation of a bracelet owned by a nurse: 4 For this implementation, a simple set-up with only one BRS for the full hospital is considered. However, in a real-life set-up, there will typically be more than one BRS component in the system, e.g., an extra BRS per department, as indicated on The existing ACCIO ontology has been further extended for this work with some key concepts and relations specific for the current use case.…”
Section: Continuous Care Ontologymentioning
confidence: 99%
See 1 more Smart Citation
“…It does not matter if some information, which is sent to the OCarePlatform, is not relevant. By using the Semantic Communication Bus (SCB) [35], the relevant information is sent to the services, which have indicated a specific interest in that type of data. As often false positives and negative are generated from single sensors or fall detection systems, the OCarePlatform is used to combine all this information and come to 1 conclusion.…”
Section: The Ocareplatformmentioning
confidence: 99%